Abandoned to manage the post-Olympic blues: Olympians reflect on their experiences and the need for a change - Bradshaw, H.; Howells, K.; Lucassen, M. (Qualitative Research in Sport, Exercise and Health, 2022)
The post-Olympic period is complex and distressing for many Olympic athletes; preparing for the likely impacts of the Olympic Games amongst returning athletes is fundamental in managing the negative responses articulated as the post-Olympic blues. Mindful of the need for the development of interventions that can support athletes, this study engaged Olympic athletes in: (a) discussing their experiences relating to the Olympic and post-Olympic periods and, (b) informing the researchers on Olympians` opinions on the management of the post-Olympic blues. Fourteen Olympic athletes from the United Kingdom took part in focus groups which were analysed using Thematic Analysis. The analysis produced six mutually exclusive themes, The Olympic Dream, The Olympic Nightmare, Commodification, Perceptions of Social Support, Limited Preparation, and Managing and Overcoming. Through these themes the Olympians provided suggestions into how the content and potential facilitation of future interventions could better support athletes through their experiences. The findings were clear, Olympic athletes irrespective of whether they had previously competed in an Olympic Games expressed a desire for support in preparing for the post-Olympic experience. They expressed that this should be delivered primarily after the Olympic Games, with several athletes highlighting the value of an awareness raising session beforehand. Athletes proposed a shift away from expert sport psychology delivery of interventions in favour of a programme which was pragmatic in terms of content and delivered by former Olympians.